Malaria-HIV co-infection: Adverse perinatal outcomes - Laar, A.K. (VDM, 2010)
This paper aims at examining the factors which influence the demand for health care services in selected Regions of Ghana. We use cross-sectional data covering 300 households in Ghana, and adopt a multinomial probit model with four health care options: self-care, drug stores, clinics, and hospitals with self-care as the base comparison group. Beside the relevant demographic, socio-economic, location, and facility-specific variables, we consider gender bias in households’ utilization of health care services. We find that married people tend to prefer care at drug stores, clinics, or hospitals to self-care. Also, urban dwellers tend to have easier access to drug stores compared to rural dwellers. Male-headed households tend to prefer self-care to any of the formal care options. We also find that, interestingly, households with more female children tend to use self-care compared to care at drug stores or hospitals while those with more adult males prefer to use drug stores during illness. This finding implies that policies aimed at promoting gender equity in health care need to consider not only the gender of the decision maker, but also the gender of individual household members.
Keywords: demand for health care; gender; gender equity; self-care; multinomial probit model